Adaption and pilot testing of a lay HIV supporter program for traditional healers: a mixed methods study in rural Uganda - Radhika Sundararajan; Matthew Ponticiello; Giselle Birch; Gabriel Nuwagaba; Rinu Alaiku; Denis Nansera; Juliet Mwanga-Amumpaire; Winnie Muyindike (Implementation Science Communications, 2023)
Abstract Background Half of people living with HIV (PLWH) in sub-Saharan Africa default from care within two years. In Uganda, and across sub-Saharan Africa, traditional healers (TH) are ubiquitous and often serve as the first line of health care. We hypothesized that with lay support training, TH could support relinkage to HIV care and ART adherence among rural Ugandan PLWH who have defaulted from HIV care. Methods Following the ADAPT-ITT framework, we adapted an evidence-based layperson HIV support program from South Africa for delivery by Ugandan TH. The ADAPT-ITT framework consists of (1) Assessment of needs; (2) Deciding which evidence-based interventions to adapt; (3) Adaptation of interventions; (4) Production of drafted adapted interventions; (5) Topical expert feedback; (6) Integration of expert feedback; (7) Training personnel; and (8) Testing the adapted intervention. The Testing phase was completed via a pilot mixed methods prospective cohort study. The study population included 12 TH practicing in Mbarara Township and 20 adult PLWH with suboptimal ART adherence (CASE adherence index score < 10) who received care from a participating TH and who resided in Mbarara Township. Primary outcome was re-linkage to HIV care within 14 days. Secondary outcomes were ART re-initiation, ART adherence, retention in care after 9 months, and implementation measures. Qualitative interviews were conducted with all participants. Results Data from the Assessment phase indicated that logistical challenges played an important role in disengagement from care among PLWH who receive care from TH, notably geographical distance to clinics and transportation costs. Additionally, HIV-related stigma and lack of social support were identified as barriers to entering and remaining in HIV care. Two core elements of the intervention were identified during the Production phase: (1) TH facilitating rapid re-linkage to HIV care and (2) TH provision of psychosocial support. In the pilot study phase, baseline median CASE adherence score was 3; only 5% of PLWH were adherent to ART via 4-day recall. The TH-delivered support achieved 100% linkage and ART initiation within 14 days, 95% ART adherence, and 100% of PLWH were retained in HIV care after 9 months. Conclusions The ADAPT-ITT framework successfully guided the adaption of a community health worker-delivered intervention for delivery by TH. TH successfully facilitated re-linkage to HIV care, support ART adherence, and retention in care for PLWH when trained as part of a lay support person program. Future studies are needed to evaluate scale-up and long-term impact.